A prebiotic mixture improved Lactobacillus acidophilus and Bifidobacterium animalis gastrointestinal in vitro resistance in petit-suisse. Issue 5 (26th April 2016) - Padilha, Marina; Villarreal Morales, Martha Lissete; Vieira, Antonio Diogo Silva; Costa, Mayra Garcia Maia; Saad, Susana Marta Isay
Abstract : Advantageous addition of a prebiotic mixture in petit-suisse cheese, improved the probiotic strains survival under gastrointestinal conditions simulated in vitro throughout 28 days of storage. Abstract : The survival of two probiotic strains – Lactobacillus acidophilus La-5 and Bifidobacterium animalis Bb-12 – incorporated into probiotic (PC) and into synbiotic (SC, with inulin + fructooligosaccharides, respectively, at 7.5 and at 2.5 g per 100 g) petit-suisse cheese was investigated in the beginning (day 1) and at the end (28 days) of storage at 4 °C when the food products were subjected to in vitro gastrointestinal simulated assays. Species-specific quantitative real time PCR (qPCR) combined with propidium monoazide (PMA–qPCR) was employed to quantify the strains. Initial La-5 and Bb-12 populations were always above 7 log CFU g −1 . The presence of the prebiotic ingredients in SC improved the Bb-12 and La-5 resistance after the 6 h assay, with higher populations in all the in vitro stages and throughout the storage period ( p < 0.05), leading to equal or superior survival rates (SR) in SC of both probiotic strains, in the beginning as well as at the end of storage. The mean La-5 SR were 58% (PC) and 67% (SC), whereas the mean Bb-12 SR were 60% (PC) and 79% (SC). Our findings suggest that the addition of a prebiotic mixture in petit-suisse cheese was advantageous, since it improved both the Bb-12 and La-5 viability and tolerance under in vitro gastrointestinal simulated conditions, both in the fresh product and in the product refrigerated for 28 days.